Assessment of Areal Average Air Quality Level over Irregular Areas: a Case Study of PM10 Exposure Estimation in Taipei (Taiwan) - Yu, Hwa-Lung; Ku, Shang-Chen; Yang, Chiang-Hsing; Cheng, Tsun-Jen; Chen, Likwang (IntechOpen, 2011)
None